PRODUCTIVITY STUDY OF HYDRAULIC BREAKER EXCAVATOR, PT HANSINDO MINERAL PERSADA, SUNGAI PINYUH DISTRICT, MEMPAWAH DISTRICT, WEST KALIMANTAN PROVINCE - Wahyudi, Tri; Nirmala, Azwa; Syafrianto, M. Khalid (Fakultas Teknik Universitas Tanjungpura, 2023)
PT Hansindo Mineral Persada is a granite mining company. Mining activities at PT Hansindo Mineral Persada use blasting and the help of a hydraulic excavator breaker to break up boulders. The crusher setting at PT Hansindo has a size of 50 cm, so rocks above 50 cm must be crushed first to make them smaller. The research aims to gain the capability of equipment production. Thus, it can assist in meeting production and cost requirements. Apart from that, this is also an effort to increase the production of hydraulic excavator breakers. Data collection in the field is carried out by observing cycle times, work constraints, working time, operational costs, the need for fuel, lubricants, etc. Then, the data is calculated on cycle time, effective working time, number of production tools, and operational costs. After that, it is necessary to make improvements during the effective working time of the obstacles that occur or to increase the number of hydraulic excavator breakers. The calculation results show that the production capacity of one hydraulic breaker excavator unit is 21.77 BCM/hour or 4,277.98 BCM/month. The operational cost for one tool is IDR 2,944,133.88/day. The increased production of the two recommended alternatives resulted in an increase of up to 4,468.41 BCM/month by improving the effective working time and 8,583.03 BCM/month by increasing the number of tools. The value of tool availability for MA increased by 0.1%, PA by 0%, UA increased by around 4%, and EU increased by around 4%.